Prevalence of smoking in northwest Iran: a meta-analysis - Mahmood Moosazadeh; Fatemeh Salami; Mahtab Movahednia; Mohammad Moqaddasi Amiri; Mahdi Afshari (Electronic Physician, 2014)
Background: Tobacco addiction is a major cause of preventable death worldwide. Thus, efforts to eliminate its use have the potential of producing significant health benefits. The purpose of this study was to conduct a meta-analysis to estimate the prevalence of cigarette smoking among people in the age range of 15 to 64. The specific objective of this meta-analysis was to provide valid data that policy makers can use to make evidence-based decisions. Methods: To determine the prevalence of smoking among the adult population in northwest Iran, we used reports published by the surveillance system used to assess the risk factors for non-communicable diseases in different provinces in northwest Iran for the years 2004 and 2006-2009. Several variables were extracted, including the years of study, gender, ages, and smoking prevalence. Based on the heterogeneity of the results, we used fixed or random effects models to estimate the overall prevalence of cigarette smoking. The analyses were performed using Stata 11 software. Results: A total of 28,436 subjects (14,248 males and 14,188 females) in five age groups, i.e., 15-24, 25-34, 35-44, 45-54, and 55-64, were interviewed. Meta-analysis in men showed that, across the age groups, the lowest prevalence was 22.9%, the highest prevalence was 26.5%, and the average prevalence was 24.7%. Among women, the lowest prevalence was 0.3%, the highest prevalence was 0.8%, and the average prevalence was 0.5%. Conclusion: We found that approximately one-fourth of males in the age range of 15-64 in northwest Iran smoked cigarettes daily. Therefore, it is necessary to conduct effective interventions to reduce the prevalence of addiction to tobacco in this area.